MATHEMATICAL STRATEGIES FOR SOLVING OPTIMIZATION PROBLEMS - N, Yogeesh; Yadav K. P, Girish; D.K, Girija; N. Raja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the subject of mathematics and computational science, the optimization-problems refer to a process of selecting a feasible alternatives solution from a set. Many of the ideas given in this paper apply to constrained parameter optimization as well. Contrary to unconstrained optimization, it is more difficult to obtain consistent numerical results, making the selection of an appropriate algorithm more complex. Optimization in finite dimensions. Early attempts to solve optimization issues on computers gave rise to the term "computer programming." “Programming” is still used in issue categories like linear and quadratic programming. So, in this paper, I aim to explore using a mathematical approach to solve optimization problems.